Determinants of Factors that Affecting Inflation in Malaysia - Rabiul Islam; Ahmad Bashawir Abdul Ghani; Emil Mahyudin; Narmatha Manickam (International Journal of Economics and Financial Issues, 2017)
Inflation became a one of the serious matters over a period of time. It can be said that, throughout the past few years, Malaysia’s inflation is caused by many factors. The aim of the paper is to determinants of factors that affecting inflation in Malaysia This paper consists of quantitative method and the econometric model is used for identify the relationship between the dependent and independent variables. It can be categorized two models in this paper namely mathematical model and econometric model. In this paper, it has been discussed the autocorrelation, multicollinearity and heteroscedasticity. High inflation may cause negative impact to a particular country.